Pengaruh Model Team Quiz Terhadap Hasil Belajar IPS Siswa Sekolah Dasar Kota Padang - Farida Farida; Audea Rinda Vandana (Jurnal Inovasi Pendidikan dan Pembelajaran Sekolah Dasar, 2019)
Model Team Quiz aims to determine the effect of the Team Quiz model on the learning outcomes of IPS students in grade IV of the elementary school year 2016/2017. This research uses an experimental research type (quasi-experiment). The population is all students of class IV SDN 10 Sungai Sapih consisting of class IV A to IV E which is determined by cluster random sampling technique so that obtained class IV A as experimental group and class IV B as a control group. The results showed that the t-test with a significant level of 5% (0.05) obtained t arithmetic (3.637)> t table (1.668). This means that there is a significant influence of the use of the Team Quiz model on the learning outcomes of IPS students of grade IV SDN 10 Sungai Sapih Kota Padang.